The first 8 weeks of the Austrian SARS-CoV-2 epidemic - Nagel, A; Łaszewska, A; Haidinger, G; Simon, J (Springer, 2021)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV‑2) reached Austria in February 2020. This study aims to describe the first 8 weeks of the Austrian epidemic and reflect on the potential mental health consequences as known at that time.